Legal Safeguards for Justice Collaborators in Murder Cases: The Richard Eliezer Verdict Analysis - Charles Ardani; Sri Astutik; Vieta Imelda Cornelis; Siti Marwiyah; Bachrul Amiq (Journal of International Multidisciplinary Research, 2025)
Justice collaborators, or "crown witnesses," have become essential in modern criminal justice systems, particularly in dismantling organized crime and uncovering complex murder cases. This study explores the legal protections afforded to justice collaborators in Indonesia through a doctrinal analysis of the Supreme Court Decision No. 1704 K/PID.SUS/2022, commonly known as the Richard Eliezer verdict. The objective is to critically examine the adequacy and application of legal safeguards provided to individuals who cooperate with law enforcement while implicated in serious crimes. Employing normative legal research methods and a statutory and case approach, the paper reveals discrepancies in the implementation of protections for justice collaborators. While the Indonesian Witness and Victim Protection Agency (LPSK) offers procedural protections, this analysis identifies significant gaps in enforcement, judicial interpretation, and institutional coordination. The findings underscore a need for stronger legislative frameworks and consistent judicial standards to uphold the rights and safety of justice collaborators. The implications extend to criminal law reform and the balancing of retributive justice with restorative mechanisms. This study contributes to the legal discourse on human rights protections in criminal procedure, particularly concerning vulnerable individuals assisting the justice system under duress or threat.